x+45x=65

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

(x+4)⋅5=5x⋅6

Simplify (x+4)⋅5.

Apply the distributive property.

x⋅5+4⋅5=5x⋅6

Simplify the expression.

Move 5 to the left of x.

5⋅x+4⋅5=5x⋅6

Multiply 4 by 5.

5x+20=5x⋅6

5x+20=5x⋅6

5x+20=5x⋅6

Multiply 6 by 5.

5x+20=30x

Move all terms containing x to the left side of the equation.

Subtract 30x from both sides of the equation.

5x+20-30x=0

Subtract 30x from 5x.

-25x+20=0

-25x+20=0

Subtract 20 from both sides of the equation.

-25x=-20

Divide each term by -25 and simplify.

Divide each term in -25x=-20 by -25.

-25x-25=-20-25

Cancel the common factor of -25.

Cancel the common factor.

-25x-25=-20-25

Divide x by 1.

x=-20-25

x=-20-25

Cancel the common factor of -20 and -25.

Factor -5 out of -20.

x=-5(4)-25

Cancel the common factors.

Factor -5 out of -25.

x=-5⋅4-5⋅5

Cancel the common factor.

x=-5⋅4-5⋅5

Rewrite the expression.

x=45

x=45

x=45

x=45

x=45

The result can be shown in multiple forms.

Exact Form:

x=45

Decimal Form:

x=0.8

Solve for x (x+4)/(5x)=6/5